Disclosing the Power and Social Class Dynamics in the Great Expectation Movie 2012 - Sofiani, Yulia; Sondari, Endang; Narawaty, Dede (STKIP PGRI Tulungagung, 2025)
The Critical Discourse Analysis (CDA) developed by Norman Fairclough is used in the present research to analyze how power and social class relations are portrayed in the 2012 movie rendition of Charles Dickens' Great Expectations. Using Fairclough's three-dimensional framework—textual analysis, discursive practice, and social practice—the study examines how Victorian England's socioeconomic hierarchies are reflected and reinforced in dialogue, and character relationships. In order to demonstrate how language and semiotics negotiate power dynamics and class hierarchies, significant events are analyzed, including Pip's transformation from a blacksmith's apprentice to a gentleman and his interactions with Estella and Miss Havisham. In order to highlight the film's applicability in the current discussions around inequality and social mobility, the study also looks at how it reframes Dickens' critique of social stratification for people today.